The Times of Our Lives: Interaction Among Different Biological Periodicities - Laje, Rodrigo; Agostino, Patricia V.; Golombek, Diego A. (Frontiers in Integrative Neuroscience, 2018)
Environmental cycles on Earth display different periodicities, including daily, tidal or annual time scales. Virtually all living organisms have developed temporal mechanisms to adapt to such changes in environmental conditions. These biological timing structures – ranging from microsecond to seasonal timing – may have intrinsic properties and even different clock machinery. However, interaction among these temporal systems may have evolutionary advantages, for example, when species are exposed to changing climatic conditions or when they expand their geographical range to different latitudes or altitudes. Here, we present and discuss a model that accounts for the circadian regulation of both ultradian (less than 24-h) and infradian (more than 24-h) cycles, and for the interaction among the three time scales. We show two clear examples of such interaction, between the circadian clock and the seasonal regulation of the hypothalamic-pituitary-thyroid axis, and between the circadian clock and the hypothalamic-nigrostriatal ultradian modulation. This remarkable interplay among the otherwise considered isolated rhythms has been demonstrated to exist in diverse organisms, suggesting an adaptive advantage of multiple scales of biological timing.